Penggunaan Metode Team Product untuk Meningkatkan Ketrampilan dan Prestasi Belajar Seni Budaya tentang Menyusun Ulasan Tertulis Keunikan Gagasan Teknik Pembuatan Fungsi dan Makna Karya Seni Rupa Siswa - Agus Supriyanto (Academy of Education Journal, 2018)
This class action research aims to find out and prove that the Team Product Method can improve the skills and achievements of students of class VIII of SMP Negeri 1 Nusawungu Semester I for the academic year 2015/2016 in learning activities in Art and Culture with material showing appreciative attitudes towards the unique ideas and techniques of art works applied archipelago. This school action research consisted of 2 cycles which were implemented in 2015 and carried out for 6 months. In this school action research the research subjects were students of class VIII D of State Junior High School 1 Nusawungu Semester I of the 2015/2016 Academic Year with a total of 32 students. Actions taken in cycles 1 and 2 are the use of the Team Product method in learning Culture and Art with material displaying an appreciative attitude towards the unique ideas and techniques of applied works of the archipelago, with observation sheets for skills and test questions as instruments. Data analysis uses comparative descriptive. Based on theoretical hypotheses and empirical mentions through the use of the Product Team method in learning Cultural Arts with material displaying an appreciative attitude towards the uniqueness of ideas and techniques of applied works of the archipelago there is an increase in the skills and learning achievement of students in class VIII D of State Junior High School 1 Nusawungu Semester I Academic Year 2015 / 2016 ie from the average initial condition value only reached 64.78 after taking action using the Team Product method in the first cycle the average value rose to 79.98 or an increase of 23.5%. Whereas in cycle 2 the grade average value increased again to 84.19 or up 5.3% from cycle 1 and 30% from the initial conditions. So both theoretically and empirically through the use of the Product Team method in learning Culture and Art with material displaying an appreciative attitude towards the unique ideas and techniques of archipelago applied art can improve learning skills and achievement from low start conditions to high end conditions.